Theo Angelopoulos’ anthropological gaze in ulysses’ gaze - Ddo. Agustín-Julián CANDADO ALONSO (Fonseca, Journal of Communication, 2023)
Ulysses’ Gaze is a 1995 movie directed by Theo Angelopoulos. In this movie we follow the footsteps of A., a ¿fictitious? Greek filmmaker who is looking for undeveloped reels that once belonged to the Manakis brothers. Besides the simplicity of the premise, we soon discover how the movie turns out to be a profound and self-conscious philosophical-anthropological reflection on identity, memory or meaning.